Coexistence of Microbial Species in Structured Communities by Forming a Hawk-Dove Game Like Interactive Relationship - Zhao, Kelei; Li, Jing; Huang, Ting; Yuan, Yang; Lin, Jiafu; Yue, Bisong; Wang, Xinrong; Chu, Yiwen (Frontiers in Microbiology, 2019)
Microorganisms evolve kinds of elaborate interaction models that can form relatively stable communities in a wide range of ecosystems. It is recognized that the spatial genetic structure of microbes in surface-attached environments lays a good foundation for the persistence of polymicrobial communities in adverse conditions. However, the interacting dynamics of microbes in facilitating the formation and stabilization of community structure still remains elusive. In this study, we identify a hawk-dove game like interspecific relationship between the two Gram-negative opportunistic pathogens Pseudomonas aeruginosa and Klebsiella pneumoniae, which naturally coexist in insect gut and can cocolonize human tissues. Specifically, although P. aeruginosa had significant competitive advantage over cocultured K. pneumoniae on solid medium with rich nutrient factors, K. pneumoniae could resist the suppression of P. aeruginosa by enhancing the expression of membrane transporters induced by the extracellular metabolites of P. aeruginosa. By contrast, under the condition that K. pneumoniae had a growth advantage but P. aeruginosa met a metabolic burden in producing quorum-sensing-controlled extracellular products, the frequency of K. pneumoniae would be slightly higher than P. aeruginosa during the coexistence because K. pneumoniae was also capable of exploiting the extracellular metabolite from P. aeruginosa. In addition, P. aeruginosa quorum-sensing variant could reap benefits from K. pneumoniae in turn and reach a relatively stable two species equilibrium. These findings provide an explanation for the formation and maintenance of polymicrobial communities in different spatially structured environments, and thus may contribute to understanding the complex interspecific interactions of microbes in local communities and shed new light on the development of social microbiology.